The organized teacher's guide to being a creative teacher - Springer, Steve; Alexander, Brandy; Persiani-Becker, Kimberly (Organized teacher series, 2019)
To keep your students engaged in the classroom, you have to get them excited about learning. This award-winning resource offers hundreds of creative ideas to reenergize your lesson plans for any subject, across all grades (K-6) from waking up the tired book report to making math fun. This new edition has been revised to align with the Common Core Standards and boosts content that is accessible online with many pages of reproducible content including worksheets, project ideas, templates for journal pages, and more. From submarine sandwich book reports to graphic organizers to help incorporating writing into math curriculum, this book has ideas and materials to add zing to your classroom plans as you incorporate the Common Core Standards.